Concurrent Bilateral Patellar Tendon Ultrasonic Debridement in a Collegiate Athlete — A Case Report. Issue 5 (May 2022) - Kruse, Ryan C.; Krill, Michael; Solsrud, Emily
Abstract : Concurrent bilateral patellar tendon ultrasonic tenotomy and debridement can be performed safely and successfully in high-level athletes.